Factors Influencing the Tendency of Fraud in the Tanggul District - Muhammad Akmal Alfarizi; Rendy Mirwan Aspirandi (Journal of Islamic Economics (JoIE), 2024)
Introduction: Fraud is a complex phenomenon that can manifest in various areas of life, including business, academics, and government. This research aims to identify the main factors that influence tendencies toward fraud, with a focus on psychological, social, and organizational aspects. Understanding these influences is essential to developing effective fraud prevention strategies. Research Methods: This study uses a factor analysis approach to examine the relationships between variables that can affect an individual or group's propensity for fraudulent behavior. These variables include internal factors, such as moral pressure, perception of risk, and the probability of gain, as well as external factors like organizational culture, the degree of supervision, and prevailing social norms. Results: Data for this research was collected through surveys and structured interviews with respondents from diverse organizational backgrounds. By applying factor analysis, the study seeks to identify the primary dimensions emerging from the data set, aiming to pinpoint the most significant factors influencing fraudulent behavior. Conclusion: In conclusion, it is hoped that the findings of this study will provide valuable insights into the factors to consider when designing effective fraud prevention strategies. The practical implications of this research include the development of more robust ethical guidelines, improvements in supervisory procedures, and the reinforcement of organizational cultures that promote integrity and transparency.